Public management of economic development under the conditions of martial law and the post-war period as a factor of economic security and sustainable development of Ukraine - Bashtannyk, Oksana; Bobrovska, Olena; Yefimenko, Liudmyla; Fimyar, Svitlana; Brazhko, Olena; Oliinyk, Nazar (Edelweiss Applied Science and Technology, 2024)
The article attempts to compare and systematize the experience of post-war reconstruction of Croatia, Serbia, and Iraq, in the very essence of their paradigms of reconstruction. The analyzed cases are refracted through the prism of the current war in Ukraine, in order to reveal actual situation in economic and sustainable development of the country and outline conceptual recommendations to apply in further processes of recovery, both in today state of armed conflict and in future reconstruction.